2019
DOI: 10.14687//jhs.v16i2.5636
|View full text |Cite
|
Sign up to set email alerts
|

Human-robot interaction: How do personality traits affect attitudes towards robot?

Abstract: The robot technology seems to be an important part of daily life and has shown great progress in recent years. Robots are used in a lot of parts of life. Thus, we need to think and know how robots will affect human life and how human will react to robots. This study focused on human’s attitude toward robots. The first purpose of this study is to determine participants’ attitude towards robots and second is to investigate how personality traits predict their attitudes towards robots. Participants consisted of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…Understanding how individuals perceive of, and respond to, social robots is a central theme of vital and continuing importance in the field of Human-Robot Interaction (HRI;HRI, 2020;Dautenhahn, 2007). Recent research suggests that this topic has special urgency given the expanding place of robotic technologies in daily life (Haegele, 2016;Beraldo et al, 2019;de Graaf et al, 2019;Liang and Lee, 2017;Morsunbul, 2019;Horstmann et al, 2018;Robb et al, 2020), and unfolding debate concerning the introduction of automation (e.g., cars, drones, robots) in society and culture (Horowitz, 2016;Floridi, 2017;Gnambs and Appel, 2019;Złotowski et al, 2017;Yogeeswaran et al, 2016). This, in turn, has lead to a reasonable degree of consensus regarding the pressing need for research to advance understanding of the underlying factors that influence people's perceptions and inferences about social robots (Appel et al, 2020;Andrist et al, 2015;Bartneck et al, 2020;Ferrari et al, 2016;Reich-Stiebert and Eyssel, 2015;Strait et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how individuals perceive of, and respond to, social robots is a central theme of vital and continuing importance in the field of Human-Robot Interaction (HRI;HRI, 2020;Dautenhahn, 2007). Recent research suggests that this topic has special urgency given the expanding place of robotic technologies in daily life (Haegele, 2016;Beraldo et al, 2019;de Graaf et al, 2019;Liang and Lee, 2017;Morsunbul, 2019;Horstmann et al, 2018;Robb et al, 2020), and unfolding debate concerning the introduction of automation (e.g., cars, drones, robots) in society and culture (Horowitz, 2016;Floridi, 2017;Gnambs and Appel, 2019;Złotowski et al, 2017;Yogeeswaran et al, 2016). This, in turn, has lead to a reasonable degree of consensus regarding the pressing need for research to advance understanding of the underlying factors that influence people's perceptions and inferences about social robots (Appel et al, 2020;Andrist et al, 2015;Bartneck et al, 2020;Ferrari et al, 2016;Reich-Stiebert and Eyssel, 2015;Strait et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative research thus far has established that individual difference variables 1 (e.g., prior robot experience, personality dispositions, and demographic characteristics) strongly affect the perceptions people have of social robots (see Eurobarometer, 2012;Kuo et al, 2009;Bartneck et al, 2007;Mutlu et al, 2006;Morsunbul, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…People who are open to experience take an interest in unusual ideas, become absorbed in the beauty of art and nature, and are interested in various domains of knowledge . Openness was a predictor for the acceptance of new technologies in general (Korukonda, 2007;Nov & Ye, 2008), and some research showed that this trait predicted positive responses to robots (Conti et al, 2017;Morsünbül, 2019;Rossi et al, 2018Rossi et al, , 2020, but see Müller & Richert, 2018). We therefore hypothesize that openness to experience predicts more positive responses to detection robots.…”
Section: Openness To Experiencementioning
confidence: 80%
“…Openness to experience, that is, a person's tendency to prefer novelty over routine and to have a broad rather than a narrow range of interests, has been found to correlate, among others, with more positive attitudes toward robots (Morsunbul, 2019), acceptance of robots (Esterwood et al, 2021), acceptance of autonomous vehicles (Gambino and Sundar, 2019;Zhang et al, 2020), and with personal innovativeness in IT (Nov and Ye, 2008). In a study on a new teleworking software (Devaraj et al, 2008), openness turned out to be the only of the "Big Five" personality factors that had a direct impact on intentions to use beyond the two core predictors (usefulness, ease of use) of the widely used Technology Acceptance Model (TAM, Davis, 1989).…”
Section: Acceptance and User Personalitymentioning
confidence: 99%